Enhancing earthquake preparedness knowledge and practice among community members in rural areas of Indonesia - Calisanie, Nyayu Nina Putri; Sansuwito, Tukimin Bin; Dioso, Regidor III; Lindayani, Linlin (TDMRC, Universitas Syiah Kuala, 2025)
This study aimed to enhance knowledge of earthquake preparedness and practice among community members in rural areas of Indonesia. In the Pacific Ring of Fire, Indonesia faces significant tectonic activity, necessitating disaster risk management. National efforts and individual involvement are crucial. However, disaster training in rural communities is limited due to limited resource allocation. The study utilized a quasi-experimental two-group pretest-posttest design in rural areas in Bandung, West Java, Indonesia, from October 2023 to January 2024. The study sample consisted of volunteers with minimum experience of at least 1 year, aged 18 years old, who were literate and willing to join in this study. The sample was selected by convenience sampling. The analysis employed a general linear model. The size was 120 for each group (240 in total). The study found that the average participant age was 27.13 (SD=3.25) years, with 52.5% having graduated from senior high school, while the control group had an average age of 26.67 4.65. The results of the analysis showed a significant interaction between groups and time spent on knowledge and practices related to earthquake preparedness. The Intervention group (IG) had a larger improvement in knowledge and practice at 2 weeks after the intervention compared to the control group (CG) ( = 5.43, p 0.001 and = 4.56, p 0.001, respectively) after correcting for confounding factors. Disaster preparedness training for volunteers in rural Indonesia effectively enhances knowledge and practice for earthquake preparedness, but further studies are needed with a more robust design and larger sample size.